Legal Protection for Doctors Performing Pregnancy Termination in Anencephaly Cases under Law Number 17 of 2023 on Health - Yusrawati Yusrawati; Dini Dewi Heniarti; A. Harits Nu'man (MASI Mandiri Edukasi, 2026)
Legal protection for healthcare professionals remains a significant issue in Indonesia, particularly regarding pregnancy termination in cases of anencephalic fetuses. Although Indonesian law permits abortion on limited grounds, including medical emergencies and pregnancies resulting from rape or other sexual violence, legal uncertainty persists when anencephaly is diagnosed after 14 weeks of gestation. This study analyzes the legal regulation of pregnancy termination in such cases and examines the legal protection available to doctors performing these procedures. Using juridical-normative and empirical-juridical approaches with a descriptive-analytical method, the study combines legal analysis with empirical data collected from 34 informants and respondents, including obstetricians, police officers, healthcare professionals, academics, religious leaders, hospital management, and legal practitioners. The findings indicate that the absence of clear operational regulations for late-detected anencephaly creates uncertainty and increases the risk of criminalization, even when procedures are performed in accordance with medical indications, informed consent, professional standards, and accredited healthcare facilities. Respondents emphasized the need for clearer procedural guidelines, stronger legal guarantees, professional protocols, and coordinated medicolegal mechanisms. The study concludes that pregnancy termination in cases of late-detected anencephaly should not automatically be treated as a criminal act when conducted by competent medical personnel in accordance with medical, ethical, and legal standards. It proposes a lex specialis-based legal protection model to strengthen legal certainty and support future health law reform in Indonesia.